Patient education interventions for adolescent and young adult kidney transplant recipients- a scoping review. - Michael Corr; Clare McKeaveney; Fina Wurm; Aisling Courtney; Helen Noble (PLoS ONE)
Background Adolescence and young adulthood are high risk periods for kidney transplant recipients. The reasons for this are complex; but are predominantly thought to be due to poor adherence to immunosuppressive medications. Patient education can help support young recipients to reduce their risk of behaviour-related transplant loss. The aim of this review was to understand what is known about education interventions targeted at adolescent and young adult kidney transplant recipients. Methods Systematic scoping review methodology was utilised. Six online databases were searched for suitable articles. Articles were selected for full text review following title and abstract screening. Articles deemed eligible to be included in the review had data extracted, which were qualitatively analysed using thematic analysis. Findings were validated through a consultation exercise with both young recipients and healthcare professionals. Results 29 studies were eligible for inclusion in the review. There was a high level of heterogeneity in the content, mode, design, and measurement of efficacy of interventions in the selected studies. Traditional face-to-face education and transition clinics were the most common educational interventions. Using technology to enhance patient education was also a major theme identified. Few studies reported using educational theory or involving patients in intervention design. Discussion Four key research gaps were identified. 1.) Lack of educational theory in intervention design 2.) Lack of patient/ stakeholder involvement 3.) Identifying best way to measure efficacy 4.) identifying novel future research questions within already well established paediatric and educational frameworks. Addressing these gaps in future research will help inform best-practice in this vulnerable population.